Inflammatory markers of antipsychotic weight gain and cardiometabolic dysfunction in youth mental health disorders - Conlan, Karen (Trinity College Dublin. School of Medicine. Discipline of Psychiatry, 2023)
Second generation antipsychotics (SGAs) are used in children and adolescents to treat psychotic symptoms in Early Onset Psychosis (EOP) and irritability and behaviours that challenge in autism spectrum disorder (ASD). Significant side effects include rapid and excessive weight gain, dyslipidaemia, insulin resistance, hyperglycaemia, and metabolic syndrome, increasing the risk of cardiovascular disease and Type 2 Diabetes Mellitus. Importantly, children appear to be at greater risk of early weight gain and metabolic dysregulation on SGAs compared to adults. Chronic low-grade inflammation has been identified in association with childhood obesity. However, there is limited understanding regarding the impact of SGAs on inflammatory markers. We hypothesized that SGA medications cause inflammation, and that this inflammation drives the associated cardiometabolic side effects. We recruited nineteen children and adolescents who were commencing SGA medication (risperidone, aripiprazole, olanzapine or quetiapine) and examined their metabolic and inflammatory profile at baseline. We measured height and weight to calculate BMI percentile. We looked at lipid profile, fasting glucose, HbA1c and prolactin levels. In serum we measured leptin, soluble CD163, TNF-α and IL-17. We cultured Peripheral Blood Mononuclear Cells (PBMCs) from the blood samples and measured TNF-α, IL-10, IL-17A and IL-17F from the cell culture supernatants. We also carried out immunophenotyping by flow cytometry to measure the frequency of specific populations of immune cells. We then followed the participants up at three, six and twelve months and repeated these measurements at each time point. A total of ten participants completed the study. Clinically, we found that the participants gained a significant amount of weight within the first three months of commencing medications and BMI percentile increased in 90% of the participants. Weight gain in the first 3 months ranged from 0.5kg to 9kg. We found that the participants with a lower BMI percentile at baseline (<50th percentile) gained more weight on SGA medication than participants with a higher BMI percentile at baseline (>50th percentile). We also found that the SGA risperidone caused a significant increase in prolactin levels of >1000 mIU/L in some participants. We examined the serum inflammatory profile of the participants at each time point using Enzyme Linked Immunosorbent Assay (ELISA). We found that leptin levels increased significantly at three months in serum. We carried out immunophenotyping by flow cytometry. To get a broad overview of immunophenotype we carried out extracellular staining to examine the frequencies of populations of immune cells. We measured T cells, Monocytes, invariant Natural Killer T (iNKT) cells, Natural Killer (NK) cells and Mucosal Associated Invariant T (MAIT) cells. We found that the frequencies of MAIT cells increased on SGA medication. We examined the cellular inflammatory profile of the participants at each time point. To do this we isolated Peripheral Blood Mononuclear Cells (PBMCs) from whole blood. We set up four conditions for culturing the cells overnight. We cultured the cells in media alone, with Lipopolysaccharide (LPS) (100ng/ml) to stimulate monocytes, with TCR beads (25ng/ml) to stimulate T-cells and with phorbol 12-myristate 13-acetate (PMA) and ionomycin (stock at 500X, used at 1X) to stimulate all immune cells. We harvested the supernatants and measured TNF-α, IL-10, IL17A and IL17F by ELISA. We found that TNF-α increased on SGA treatment in the supernatants of PBMCs stimulated with LPS at 3 months, IL17A increased on SGA treatment in the supernatants of PBMCs stimulated with TCR beads at 3 months and IL-10 increased on SGA treatment in the supernatants of non-treated PBMCs at all time points. We investigated the cellular source of these cytokines using intracellular flow cytometry by staining PBMCs at each time point and we found that MAIT cells were increased and were producing more IL-17 and TNF-α on SGA medication. As SGAs are dopamine antagonists, we also investigated the effect dopamine had on cytokine production. To do this we used a monocyte cell line and cultured the cells in dopamine hydrochloride (100µM) both with and without LPS (100ng/ml). We found that dopamine alone caused a significant reduction in TNF-α production. We cultured PBMCs in dopamine hydrochloride +/- TCR beads (25ng/ml) +/- PMA (stock at 500X, used at 1X), and in risperidone (1µg/ml) +/- TCR beads +/- PMA. We carried out intracellular flow cytometry and measured TNF-α production by ELISA. We found that both dopamine and risperidone caused a significant reduction in TNF-α production. Collectively these findings suggest that within three months of starting an SGA these children and adolescents developed an inflammatory phenotype. We found that the same driver of metabolic disease in the form of an inflammatory phenotype that occurs in childhood obesity also occurs during treatment with SGA medications. This indicates that early inflammation could be a possible mechanism for the weight gain and metabolic dysfunction that occurs in patients who are on SGA medications. In conclusion, this study gives us an understanding of some of the immunological underpinnings of the metabolic complications associated with SGAs. Future research could potentially identify novel targets to combat this inflammation and may lead to a reduction in metabolic side effects.
Keywords: obesity; inflammation; cardiometabolic dysregulation; antipsychotics; children; mental illness